2015
DOI: 10.4236/jmmce.2015.32012
|View full text |Cite
|
Sign up to set email alerts
|

Strength Characteristics of Inoculated and Nodularised Thin Wall Ductile Iron Castings

Abstract: Carbide precipitates in Thin Wall Ductile Iron (TWDI) used for automotive applications needs to be eliminated or reduced for improved strength, ductility, crack propagation resistance and good machinability. Ductile iron thin section profiles (≤3 mm) present danger of massive carbide precipitations in the as-cast sample. Precipitated carbide phase is brittle and negatively affects the mechanical properties of the iron matrix. The suppression of carbide formation is associated with the nucleating properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…These microstructures also fol- inoculant. This is so Ce-Ca-Al-S-O-FeSi containing inoculant has higher nodularity may be due to formation of cerium-calcium-sulphides and oxides during solidification [13,14]. It may be also noted from energy dispersive spectrometer (EDS) profile and elemental analysis that the CeO 2 and Ce 2 S 3 is observed near to the nodule point and is missing away from the nodule point.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…These microstructures also fol- inoculant. This is so Ce-Ca-Al-S-O-FeSi containing inoculant has higher nodularity may be due to formation of cerium-calcium-sulphides and oxides during solidification [13,14]. It may be also noted from energy dispersive spectrometer (EDS) profile and elemental analysis that the CeO 2 and Ce 2 S 3 is observed near to the nodule point and is missing away from the nodule point.…”
Section: Resultsmentioning
confidence: 95%
“…It has been observed that Ce-Ca-Al-S-O-FeSi for one step in-mould inoculation at 0.4 wt% contain pearlitic matrix having ultimate tensile strength (UTS) and percentage of elongation are 720 ± 3 MPa and 4.5 ± 3% which are higher than Zr-Mn-Ca-Al-Ba-Fe-Si (UTS and % elongation 655 ± 5 MPa and 3.3 ± 5%) and Sr-Al-Ca-FeSi (UTS and % elongation 557 ± 5 MPa and 2.3 ± 5%) respectively shown in Table 4. This is so because of carbon diffusion towards graphitization centre may due to formation of cerium-calcium-sulphides and oxides, promote the volume fraction of ferrite sample inoculated by (a) Ce-Ca-Al-S-O-FeSi, b) Zr-Mn-Ca-Al-Ba-FeSi and c) Sr-Al-Ca-FeSi increases more and volume fraction of pearlite decreases less in Ce-Ca-Al-S-O-FeSi containing inoculant [13,14]. The fracture analysis of 2 mm containing inoculants at 0.4 wt% during one step in-mould inoculation shows the mixed mode of fracture i. e. ductile and brittle fracture observed and the ductile nature of fracture can be seen more in the plates inoculated with 0.4 wt% inoculants with Ce-Ca-Al-S-O-FeSi containing inoculant.…”
Section: Tensile Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2 mm section thickness of EDS morphology inoculated by (a) Ce bearing Fe-Si alloy (b) Zr bearing Fe-Si alloy and (c) Sr bearing Fe-Si alloy at 0.4wt% one step in mould inoculation have been shown in Figure 5. It has been observed that graphite nodularity of Ce bearing Fe-Si alloy has more than Zr bearing Fe-Si alloy and Sr bearing FeSi alloy may due to formation of cerium-calcium-sulphides and oxides during solidification (Riposan, Chisamera, Uta, Stan, Naro, & Williams, 2014;Ochulor, Adeosun, Amuda, & Balogun, 2015).…”
Section: Microscopic Observationmentioning
confidence: 99%
“…Riposan, Chisamera, Uta, Stan, Naro, and Williams (2014) have investigated that the addition of rare earth elements during in-mould inoculation provides control of casting hardness and improve graphite quality. Ochulor, Adeosun, Amuda, and Balogun (2015) found that two step inoculation methods provide better nodule count and nodularity with 2, 3 and 4 mm thin plate thickness respectively. Upadhyaya, Singh, and Kumar (2017) proposed that Ce bearing Fe-Si alloy at 0.4 % reducing under-cooling to improve nodularility and nodule count in thin plate casting thickness.…”
Section: Introductionmentioning
confidence: 96%